2012
DOI: 10.1001/archgenpsychiatry.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Symptoms in Adolescence Index Risk for Suicidal Behavior

Abstract: CONTEXT Recent evidence from both clinical and population research has pointed to psychotic symptoms as potentially important markers of risk for suicidal behavior. However, to our knowledge, there have been no epidemiological studies to date that have reported data on psychotic symptoms and suicidality in individuals who have been clinically assessed for suicidal behavior. OBJECTIVES To explore associations between psychotic symptoms in nonpsychotic adolescents and risk for suicidal behavior in (1) the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 153 publications
(62 citation statements)
references
References 51 publications
4
56
2
Order By: Relevance
“…The study members with these early psychotic symptoms also had a range of other outcomes in adulthood including anxiety, depression and substance dependence, with only one escaping reasonably unscathed. Worryingly, these children were also more likely to attempt or complete suicide during adolescence or adulthood, consistent with a recent study of Irish adolescents (Kelleher et al 2012c). …”
Section: Discussionsupporting
confidence: 89%
“…The study members with these early psychotic symptoms also had a range of other outcomes in adulthood including anxiety, depression and substance dependence, with only one escaping reasonably unscathed. Worryingly, these children were also more likely to attempt or complete suicide during adolescence or adulthood, consistent with a recent study of Irish adolescents (Kelleher et al 2012c). …”
Section: Discussionsupporting
confidence: 89%
“…26 In a community-based study of adolescents, those with psychiatric disorders who reported psychotic experiences (predominantly AVH) had a far higher prevalence of suicidal behavior than those with psychopathology who did not report psychotic experiences. 25 Adolescents with a diagnosis of MDD who reported psychotic experiences, eg, had a 14-fold increase in suicide plans or attempts compared to adolescents with the same diagnosis who did not report psychotic experiences. In a prospective cohort study, AVH were also investigated as a clinical predictor of future suicide attempts in community-based adolescents.…”
Section: The Epidemiology and Phenomenology Of Hallucinations In Chilmentioning
confidence: 99%
“…24 Additionally, psychotic symptoms predicted more severe psychopathology from a number of perspectives in addition to multimorbidity, in terms of both global and cognitive functioning. 25 …”
Section: The Epidemiology and Phenomenology Of Hallucinations In Chilmentioning
confidence: 99%
“…The presence of self‐reported psychotic‐like experiences (PEs), which do not reach the threshold for a diagnosable psychotic disorder, may be associated with an elevated risk for developing psychotic disorders in the future (Fusar‐Poli et al, 2013). However, limited evidence also suggests that PEs are associated with impacts on mood, functioning, and suicidality, indicating that these symptoms might carry wider implications for public mental health than for the development of psychosis alone (Armando et al, 2012; Fusar‐Poli et al, 2014; Kelleher et al, 2012a; Kelleher et al, 2014a; Yung et al, 2006). This leads us to hypothesise that people with PEs could be greater consumers of mental health services, including primary care, compared to those without (DeVylder et al, 2014).…”
Section: Introductionmentioning
confidence: 99%